Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557277
|View full text |Cite
|
Sign up to set email alerts
|

How technology supports family communication in rural, suburban, and urban kenya

Abstract: Much ICTD research for sub-Saharan Africa has focused on how technology related interventions have aimed to incorporate marginalized communities towards global economic growth. Our work builds on this. We present results from an exploratory qualitative study on the family communication practices of family members who communicate both within and between rural, suburban, and urban settings in Kenya. Our findings reveal that family communication focuses on economic support, well-being, life advice, and everyday c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Next, the focus group findings support prior literature which point out that migrant workers tend to prioritize hearing updates about their families [5]. As such, they often have limited opportunities to share about their own experiences, despite the fact that they have a strong desire to.…”
Section: Challenges Faced By Domestic Helperssupporting
confidence: 77%
See 1 more Smart Citation
“…Next, the focus group findings support prior literature which point out that migrant workers tend to prioritize hearing updates about their families [5]. As such, they often have limited opportunities to share about their own experiences, despite the fact that they have a strong desire to.…”
Section: Challenges Faced By Domestic Helperssupporting
confidence: 77%
“…As a final example, Odour et al present an exploratory qualitative study on how technology supports family communication in different parts of Kenya. Similar to the other papers, they found that communication for such families typically revolves around "economic support, life advice and the everyday coordination of activities", leaving such families with limited opportunities for the sharing of personal experiences [5].…”
Section: Use Of Technologies By Migrant Familiessupporting
confidence: 69%
“…For instance, phone use in Kenya is effected by elder sons' social and cultural obligations to facilitate family information flow (e.g. Oduor et al 2014). However, often phenomena linking technology use, oral practices and social roles are assigned to other analytic categories.…”
Section: Oral Practices and The Selfhood Of A Communitymentioning
confidence: 99%
“…Exclusionary modes and genres also undermine the mutually supportive communications and ethos of co-operation that enable people in low-income communities in Africa to survive (e.g. [45,31]. In fact, parents' concerns about clandestine communications amongst MXit users [10], and the literacies associated with MXit use, contributed to demonising the platform [13].…”
Section: Communication Practicesmentioning
confidence: 99%
“…Older people use Callback for alerts and younger people for free texts that they do not expect older family members, or their intermediaries, to read. Oduor et al [30] suggest tailoring phone functionality to different responsibilities in Kenyan families based on insights from culturally-sensitive interviews that showed that eldest children and the siblings of widows are socially obliged to stay aware of family members' activities and coordinate information exchange [31]. In Mankosi roles related to gender, age and birth-order also include representing families in community decision-making.…”
Section: Generational Differencesmentioning
confidence: 99%